Point-of-care testing for HIV and sexually transmitted infections reveals risky behavior among men at gambling centers in Uganda - Kiragga, Agnes N.; Bwanika, John M.; Kyenkya, Joshua; Banturaki, Grace; Kigozi, Joanita; Musinguzi, Davis; Namimbi, Florence; Chander, Geetanjali; Reynolds, Steven J.; Manabe, Yukari C. (International journal of STD & AIDS, 2021)
In sub-Saharan Africa (SSA), men are generally difficult to engage in healthcare programs. However, sports gambling centers in SSA can be used as avenues for male engagement in health programs. We offered point-of-care HIV and syphilis testing for men located at five gambling centers in Uganda and assessed HIV risky sexual behavior. Among 507 men, 0.8% were HIV-positive and 3.8% had syphilis. Risky sexual behavior included condomless sex with partner(s) of unknown HIV status (64.9%), having multiple sexual partners (47.8%), engaging in transactional sex (15.5%), and using illicit drugs (9.3%). The majority at 64.5% were nonalcohol consumers, 22.9% were moderate users, and 12.6% had hazardous consumption patterns. In 12 months of follow-up, the incidence rate of syphilis was 0.95 (95% CI: 0.82-1.06) among 178 men. Thus, men in SSA have a high prevalence of syphilis and risky sexual behavior which should be more effectively addressed to reduce the risk of HIV acquisition.
Keywords: Syphilis (treponema pallidum); Africa; High-risk behavior; Men; HIV (human immunodeficiency virus)